Новый курс лекций по социологии спорта - Кильдюшов, Олег (Социологическое обозрение, 2015)
Ansgar T., Seiberth K., Mayer J. Sportsoziologie: Ein Lehrbuch in 13 Lektionen. Aachen: Meyer & Meyer Verlag, 2013. 383 S. (sportwissenschaft Studieren, 8). ISBN 978-3-89899-639-6